The dynamic genome and transcriptome of the human fungal pathogen Blastomyces and close relative Emmonsia (2015)
ABSTRACT: Three closely related thermally dimorphic pathogens are causal agents of major fungal diseases affecting humans in the Americas: blastomycosis, histoplasmosis and paracoccidioidomycosis. Here we report the genome sequence and analysis of four strains of the etiological agent of blastomycosis, Blastomyces, and two species of the related genus Emmonsia, typically pathogens of small mammals. Compared to related species, Blastomyces genomes are highly expanded, with long, often sharply demarcated tracts of low GC-content sequence. These GC-poor isochore-like regions are enriched for gypsy elements, are variable in total size between isolates, and are least expanded in the avirulent B. dermatitidis strain ER-3 as compared with the virulent B. gilchristii strain SLH14081. The lack of similar regions in related species suggests these isochore-like regions originated recently in the ancestor of the Blastomyces lineage. While gene content is highly conserved between Blastomyces and related fungi, we identified changes in copy number of genes potentially involved in host interaction, including proteases and characterized antigens. In addition, we studied gene expression changes of B. dermatitidis during the interaction of the infectious yeast form with macrophages and in a mouse model. Both experiments highlight a strong antioxidant defense response in Blastomyces, and upregulation of dioxygenases in vivo suggests that dioxide produced by antioxidants may be further utilized for amino acid metabolism. We identify a number of functional categories upregulated exclusively in vivo, such as secreted proteins, zinc acquisition proteins, and cysteine and tryptophan metabolism, which may include critical virulence factors missed before in in vitro studies. Across the dimorphic fungi, loss of certain zinc acquisition genes and differences in amino acid metabolism suggest unique adaptations of Blastomyces to its host environment. These results reveal the dynamics of genome evolution and of factors contributing to virulence in Blastomyces.